N-Arylsulfonyl-α-amino carboxamides are potent and selective inhibitors of the chemokine receptor CCR10 that show efficacy in the murine DNFB model of contact hypersensitivity. Issue 21 (1st November 2016) - Abeywardane, Asitha; Caviness, Gary; Choi, Younggi; Cogan, Derek; Gao, Amy; Goldberg, Daniel; Heim-Riether, Alexander; Jeanfavre, Debra; Klein, Elliott; Kowalski, Jennifer A.; Mao, Wang; Miller, Craig; et al.
Graphical abstract: Abstract: Compound1 ((4-amino-3, 5-dichlorophenyl)-1-(4-methylpiperidin-1-yl)-4-(2-nitroimidazol-1-yl)-1-oxobutane-2-sulfonamido) was discovered to be a 690 nM antagonist of human CCR10 Ca 2+ flux. Optimization delivered (2 R )-4-(2-cyanopyrrol-1-yl)- S -(1 H -indol-4-yl)-1-(4-methylpiperidin-1-yl)-1-oxobutane-2-sulfonamido (eut-22 ) that is 300 fold more potent a CCR10 antagonist than1 and eliminates potential toxicity, mutagenicity, and drug–drug-interaction liabilities often associated with nitroaryls and anilines.eut-22 is highly selective over other GPCR's, including a number of other chemokine receptors. Finally, eut-22 is efficacious in the murine DNFB model of contact hypersensitivity. The efficacy of this compound provides further evidence for the role of CCR10 in dermatological inflammatory conditions.